Ekonomi Digital di Indonesia: Peluang, Dampak, dan Tantangan - Fortuna, Armyalin Dewi (Maliki Interdisciplinary Journal, 2026)
Indonesia’s digital economy is experiencing rapid growth, driven by the increasing use of the internet, smartphones, and various platform-based services. This development opens up significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their market reach, improve operational efficiency, and reduce marketing costs through the use of digital marketing and e-commerce. However, the transformation to a digital economy also presents various challenges, such as the digital literacy gap, data security issues, and increasing competition. This article aims to examine the development of the digital economy in Indonesia, analyze its impact on MSMEs, and identify the various challenges faced in the adaptation process. This research uses a qualitative approach with a literature review method, referencing various national journals, including academic publications from UIN Maulana Malik Ibrahim Malang, to produce a comprehensive and scientifically based discussion.